On the global generalized solvability of a chemotaxis model with signal absorption and logistic growth terms. (12th April 2019) - Lankeit, Elisa; Lankeit, Johannes
Abstract: Introducing a suitable solution concept, we show that in bounded smooth domains, , the initial boundary value problem for the chemotaxis system with homogeneous Neumann boundary conditions and widely arbitrary initial data has a generalized global solution for any .